Sistem Pengeolahan Limbah Cair Pada Kolam Pengendapan Lumpur I (KPL I) Menggunakan Metode Waste Water Treatment Plant PT. X - Ahmad Yori Tegar Pratama; Panisean Nasution; Natalina Natalina (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This internship report discusses the wastewater treatment system at Sedimentation Pond I (KPLI) using the Waste Water Treatment Plant (WWTP) method at PT X, Tarahan Port Unit. The objective is toanalyze the wastewater treatment process to meet the Environmental Quality Standards (BML) as regulatedin Lampung Province Regional Regulation No. 11 of 2012. The WWTP process includes several stages,from initial sedimentation in KPL, chemical processes (coagulation, flocculation, and filtration), tomonitoring key water quality parameters such as pH, TSS, Fe, and Mn. Results show that the WWTP systemis highly efficient in reducing pollutants and maintaining wastewater quality to prevent environmentalcontamination. Despite challenges such as high operational costs and sludge accumulation, the system isproven to be effective in supporting environmental sustainability in the mining port area.